The Overplay Functions and Authority of The Sea Security Board (Bakamla) and The Sea and Coast Guard in Keeping Marine Security in Indonesia - Suparto Suparto; Admiral Admiral (Fakultas Hukum Universitas Mataram, 2022)
Indonesia is a maritime country with a wide ocean. Geopolitically, Indonesia’s position is an international shipping lane. Therefore, it is necessary to have an institution that has the duty and authority to maintain sea and coastal security and shipping safety. The formulation of the problem is how the functions and authorities of the Sea and Coast Guard (SCG) and the Maritime Security Agency (Bakamla) are in guarding Indonesian seas. The research method used a normative juridical approach with secondary data and analyzed descriptively qualitatively. There are two overlapping institutions in carrying out their duties and functions, namely SCG which is regulated in Law No. Year 2008 concerning Shipping and Bakamla which is regulated under the Law No. 32 Year 2014 concerning Marine Affairs. The government intends that maritime security in Indonesia to be handled by the military, not civilians. This can be seen that the chairman of Bakamla is held by a general from the Indonesian Navy and is responsible to the President through the Coordinating Minister for Political, Legal and Security Affairs. While in Law No. 17 Year 2008 stipulates that SCG is under the Ministry of Transportation and is responsible to the President. Bakamla is more appropriate to be used as SCG, this is based on the consideration that Indonesia is a maritime country with wide seas with all its problems such as narcotics trafficking, human trafficking, terrorism, theft of marine resources, etc., so it would be more appropriate to submit it to Bakamla as a semi-official institution. military. As a consequence of this choice, it is necessary to revise Law No. 17 Year 2008 and Law No. 32 Year 2014.